KEPEMILIKAN SAHAM PUBLIK DAN RETURN ON ASSETS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Shifa Putri Hamdani; Willy Sri Yuliandari; Eddy Budiono (JRAK, 2017)
The Corporate Social Responsibility (CSR) in the company recently is not only based on the single bottom line which depends only on the financial condition, but also on the triple bottom line which also depends on the financial condition, environment and society. This study aims to get empirical evidence about the influence of public ownership and Return on Assets (ROA) on the disclosure of Corporate Social Responsibility. The object of the research is a service company listed on the Indonesia Stock Exchange in 2014-2015. Collection methods used in this research is the data sourced in an annual report published by the Indonesia Stock Exchange. The collection of samples used is purposive sampling technique. Total sample of this research are 9 service companies listed in Indonesia Stock Exchange in 2014-2015. Simultaneously, public ownership and ROAgave significant effect to CSR disclosure. Partially, public ownershipgave adversely affect to the direction of CSR disclosure. ROA effect with positive direction towards CSR.